Fungsi Manajemen Kepala Ruangan dan Karakteristik Perawat Dengan Penerapan Identifikasi Pasien - Yessi Fadriyanti; Yosi Suryarinilsih; Efitra Efitra (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2021)
One of the goals of patient safety is patient identification. The mistakes in identifying patients can increase KTD cases which have an impact on decreasing the service quality. This study aimed to see the relationship between the management function of the nursery room leader and the characteristics of nurses toward the application of patient identification. The research method used was quantitative research, with a cross sectional study approach. The respondents in this study amounted to 51 people. The data analysis technique used univariate analysis and bivariate analysis. The results showed that the application of patient identification in the nurses at Padang Hospital was still lacking.